Campylobacter concisus – A New Player in Intestinal Disease - Kaakoush, Nadeem O.; Mitchell, Hazel M. (Frontiers in Cellular and Infection Microbiology, 2012)
Over the last decade Campylobacter concisus, a highly fastidious member of the Campylobacter genus has been described as an emergent pathogen of the human intestinal tract. Historically, C. concisus was associated with the human oral cavity and has been linked with periodontal lesions, including gingivitis and periodontitis, although currently its role as an oral pathogen remains contentious. Evidence to support the role of C. concisus in acute intestinal disease has come from studies that have detected or isolated C. concisus as sole pathogen in fecal samples from diarrheic patients. C. concisus has also been associated with chronic intestinal disease, its prevalence being significantly higher in children with newly diagnosed Crohn’s disease (CD) and adults with ulcerative colitis than in controls. Further C. concisus has been isolated from biopsy specimens of patients with CD. While such studies support the role of C. concisus as an intestinal pathogen, its isolation from healthy individuals, and failure of some studies to show a significant difference in C. concisus prevalence in subjects with diarrhea and healthy controls has raised contention as to its role in intestinal disease. Such findings could argue against the role of C. concisus in intestinal disease, however, the fact that C. concisus strains are genetically diverse raises the possibility that differences exist in their pathogenic potential. Evidence to support this view comes from studies showing strain specific differences in the ability of C. concisus to attach to and invade cells and produce virulence factors, including toxins and hemolytic phospholipase A. Further, sequencing of the genome of a C. concisus strain isolated from a child with CD (UNSWCD) and comparison of this with the only other fully sequenced strain (BAA-1457) would suggest that major differences exist in the genetic make-up of this species which could explain different outcomes of C. concisus infection.